2018
DOI: 10.20414/edulangue.v1i2.262
|View full text |Cite
|
Sign up to set email alerts
|

Use of Course Review Horray (CRH) Strategy to Promote Students' Self-Confidence in Learning Vocabulary

Abstract: This research aims at finding out whether Course Review Horray strategy has effect to promote students’ self-confidence in learning vocabulary at the seventh grade students of MA NW Senyiur Keruak Lotim or not. This research rises since the use of English vocabulary plays crucial roles of mastering English language. Students will gain a huge number of benefits in which they can cope with various vocabulary items. For instance; students will automatically convince their self to speak up fluently where they know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The result of this study added the proof that the implementations of course review horay could increase the students' skills in learning English. This study result completed the study results by Kamarudin et al (2018) increasing the students' self confidence in learning vocabulary and by Masruddin (2019) increasing students' speaking skill. Automatically, the study result becomes more complete because the previous studies were conducted in the classes of vocabulary and speaking while the present study was implemented in grammar class.…”
Section: Course Review Horay Model As a More Effective Model For Teaching Grammarsupporting
confidence: 54%
See 2 more Smart Citations
“…The result of this study added the proof that the implementations of course review horay could increase the students' skills in learning English. This study result completed the study results by Kamarudin et al (2018) increasing the students' self confidence in learning vocabulary and by Masruddin (2019) increasing students' speaking skill. Automatically, the study result becomes more complete because the previous studies were conducted in the classes of vocabulary and speaking while the present study was implemented in grammar class.…”
Section: Course Review Horay Model As a More Effective Model For Teaching Grammarsupporting
confidence: 54%
“…There were still limited studies related to the implementation of course review horay (CRH) in English teaching and learning process. One of them is a study by Kamarudin et al (2018) who found that CRH could improve students' self confidence in the teaching and learning of vocabulary. Meanwhile, Masruddin (2019) had showed the result of his study that CRH was able to develop students' speaking skill.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There's a lot more to vocabulary than just a series of words (Kamarudin et al, 2018). Thus, in order to make vocabulary learning effective, a learner must be in a sufficient condition that would help him obtain, understand, and produce the language.…”
Section: Vocabulary Masterymentioning
confidence: 99%
“…Besides, Puspitaningrum & Arlianty (2019) argue that CRH contains a game inside its learning process. Related to the implementation of CRH in the teaching and learning process, Kamarudin et al (2018) and Masruddin (2019) present the steps to be done by the teachers as follows. First of all, the teacher should set the learning goal.…”
Section: Course Review Horaymentioning
confidence: 99%